Penerapan Model Pembelajaraan Kooperatif Tipe Explicit Instruction Dalam Meningkatkan Hasil Belajar IPA Siswa Kelas IV SD - Satriani Satriani (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
This study aims to describe the application of the explicit instruction cooperative learning model in improving science learning outcomes for fourth-grade students of SD Inpres 4/82 Biru, Tanete Riattang District, Bone Regency. The approach used in this research is a descriptive qualitative approach with classroom action research. The focus of research, namely the application of the Explicit Instruction type cooperative learning model and student learning outcomes. The research setting was SD Inpres 4/82 Biru, Tanete Riattang District, Bone Regency. The research subjects were all students in grade IV SD Inpres 4/82 Biru, Tanete Riattang District, Bone Regency, totaling 17 students consisting of 11 male students and 6 female students. Data collection techniques and procedures used were tests, observation, and documentation. The research data were analyzed using qualitative data analysis techniques, namely data reduction, data presentation, data verification, and concluding. The results showed that there was an increase in learning outcomes in each cycle. The results of the first cycle were in the moderate category (C) and increased in the second cycle with the good category (B). This study concludes that the application of the Explicit Instruction type cooperative learning model can improve the results of fourth-grade students' science learning outcomes SD Inpres 4/82 Biru, Tanete Riattang District, Bone Regency.